My letter and your letter: The development of Icelandic children's letter-knowledge between ages four and six - Oddsdóttir, Rannveig; Ragnarsdóttir, Hrafnhildur (Menntavísindasvið Háskóla Íslands, 2022)
Knowing the letters of the alphabet and letter-sound correspondences are important foundation skills for children´s literacy development. Preschool children´s letter-knowledge has been found to predict reading performance in the first years of schooling. Formal reading instruction begins at different ages in different countries. In the UK and USA, the starting age is around age four in kindergarten while in many European countries, including Iceland, formal reading instruction starts in first grade, at age six. However, children do not only learn letters in school, they also learn about letters from their parents and in their daily life. Letter-knowledge in preschool has been found to be correlated to factors like socioeconomic status of the family and the home literacy environment. Research on young children´s letter-knowledge confirms that it is not a matter of chance which letters they first learn, some letters seem to be easier to learn than others. Most children, for example, learn their own and their family members´ initials first and English- speaking children are more likely to know the letters B, X, O and A than V, U, N and G. It is not fully known what determines why some letters are learned before others. However, factors such as their order in the alphabet, their prevalence in the written language and how clear their corresponding sounds are might have something to do with it.The aim of this study was to explore Icelandic children´s letter-knowledge. The main research questions were the following: How does children´s letter knowledge develop between ages four and six? Are some letters learned before others and if so, which letters? Is Icelandic children´s letter-knowledge influenced by parents´ SES, literacy environment in their homes and/or by their language skills? How does the letter knowledge of children who know few letters at age 4 and 5 develop, and do children who still know few letters at the end of first grade have common characteristics in terms of SES, their home literacy environment or ...